The Ruling on Implementing Retribution Between Male and Female: A Comparative Jurisprudential Study under Omani Law - Alshahri, Ali Said Ali Ghafram; Alshahri, Ahmed Mohammed Ali Ghafram (Journal of Islamic Sciences, 2025)
This research aims to clarify the ruling on the implementation of Retribution (retributive justice) between males and females in Islamic jurisprudence by comparing the opinions of the major Islamic schools of thought (Ibadhis, Hanafis, Malikis, Shafi’is, and Hanbalis). The study also examines the application of Retribution in Omani law. The researchers employed inductive, descriptive, analytical, and comparative methodologies. The key findings indicate that Retribution is the act of the victim or their legal guardian inflicting upon the offender an equivalent or similar punishment. Scholars unanimously agree on the permissibility of enforcing Retribution between men and women in cases of intentional homicide, while they differ regarding non-lethal injuries. And that there is no explicit provision in Omani law that addresses execution as a form of retribution; rather, it is mentioned implicitly. The Omani law does not differentiate between men and women in the application of the death penalty except in one specific case. The study concludes with a recommendation to Omani legislators to consider the situation of a woman sentenced to death if she is in her legally prescribed waiting period (‘iddah) due to the death of her husband, in which case the execution should be postponed until the completion of the ‘iddah.